2019
DOI: 10.21315/mjms2019.26.1.6
|View full text |Cite
|
Sign up to set email alerts
|

SEMA3B but Not CUL1 as Marker for Pre-Eclampsia Progression

Abstract: BackgroundAn imbalance between pro- and anti-angiogenic factors contributes to impaired trophoblast invasion during pregnancy, leading to failure of uterine spiral artery remodeling, blood vessel ischemia, and pre-eclampsia (PE). Anti-angiogenic semaphorin 3B (SEMA3B) and pro-angiogenic cullin 1 (CUL1) are expressed in both the placenta and maternal blood. The present study investigated correlations between serum and placental SEMA3B as well as CUL1 levels in late-onset PE.MethodsThis cross-sectional study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…36 SEMA3B, the sense-cognate gene for SEMA3B-AS1, belongs to the SEMAs and is involved in different biological processes, such as apoptosis, cell invasion, cell migration, and angiogenesis. 37 In our study, we found that the RNA levels of SEMA3B-AS1 and SEMA3B in CRC were significantly correlated. Notably, a change in SEMA3B-AS1 abundance through overexpression and knockdown particularly affected SEMA3B mRNA and protein expression.…”
Section: F I G U R E 5 Sema3b-as1 Requires Ep300/sema3b To Suppress C...supporting
confidence: 52%
See 1 more Smart Citation
“…36 SEMA3B, the sense-cognate gene for SEMA3B-AS1, belongs to the SEMAs and is involved in different biological processes, such as apoptosis, cell invasion, cell migration, and angiogenesis. 37 In our study, we found that the RNA levels of SEMA3B-AS1 and SEMA3B in CRC were significantly correlated. Notably, a change in SEMA3B-AS1 abundance through overexpression and knockdown particularly affected SEMA3B mRNA and protein expression.…”
Section: F I G U R E 5 Sema3b-as1 Requires Ep300/sema3b To Suppress C...supporting
confidence: 52%
“…ZEB1‐AS1 activated the expression of ZEB1 in prostate cancer 36 . SEMA3B, the sense‐cognate gene for SEMA3B‐AS1 , belongs to the SEMAs and is involved in different biological processes, such as apoptosis, cell invasion, cell migration, and angiogenesis 37 . In our study, we found that the RNA levels of SEMA3B‐AS1 and SEMA3B in CRC were significantly correlated.…”
Section: Discussionmentioning
confidence: 48%